2015
DOI: 10.1103/physrevb.91.245434
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and mechanical properties of carbyne

Abstract: The atomic structure and mechanical properties of the carbyne (monatomic linear chains), containing from 2 to 21 carbon atoms, are theoretically investigated by ab-initio methods. We demonstrate the existence of a stable cumulene-structure in the inner part of chains with the number of atoms N>=10. We present a general stress-strain diagram of chains until the moment when they break, which enables to determine their strength, elasticity and fragility. For chains with N>=4, the relationship between the strength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…The structures that take place before the bifurcation are completely similar to those discussed in [4,5]. It can be seen from Fig.…”
Section: Static Bi-structure In the Dft-modelsupporting
confidence: 66%
See 2 more Smart Citations
“…The structures that take place before the bifurcation are completely similar to those discussed in [4,5]. It can be seen from Fig.…”
Section: Static Bi-structure In the Dft-modelsupporting
confidence: 66%
“…Most of these methods are based on the density functional theory [1][2][3], implemented in a number of powerful computational packages, such as ABINIT, Quantum Espresso, VASP, and others. Many interesting results were obtained in this way [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…() observed and calculated a strain‐induced metal–semiconductor transition, and Timoshevskii et al. () reported a theoretical study of the atomic structure and mechanical properties. Further theoretical insights should be expected from the application of WFs to the investigation of localized states in these one‐dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Fei et al [30] presented the quasiparticle energy and optical absorption by using ab initio many-body approaches. More recently, Huang et al [31] investigated plasmonlike resonances, La Torre et al [32] observed and calculated a strain-induced metal-semiconductor transition, and Timoshevskii et al [33] reported a theoretical study of the atomic structure and mechanical properties. Further theoretical insights should be expected from the application of WFs to the investigation of localized states in these one-dimensional structures.…”
mentioning
confidence: 99%